2015
DOI: 10.1371/journal.pone.0141797
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Induces a Prothrombotic State Independently of the Physical Activity

Abstract: Hypoxia (oxygen deprivation) is known to be associated with deep vein thrombosis and venous thromboembolism. We attempted to get a better comprehension of its mechanism by going to high altitude, thereby including the potential contributing role of physical activity. Two groups of 15 healthy individuals were exposed to hypoxia by going to an altitude of 3900 meters, either by climbing actively (active group) or transported passively by cable car (passive group). Both groups were tested for plasma fibrinogen, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 37 publications
3
42
0
Order By: Relevance
“…Hypoxia is known to be associated with deep vein thrombosis [ 44 ] and venous thromboembolism [ 45 ]. The link between long-haul air travel and venous thromboembolism is a subject of continuing debate [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is known to be associated with deep vein thrombosis [ 44 ] and venous thromboembolism [ 45 ]. The link between long-haul air travel and venous thromboembolism is a subject of continuing debate [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…During conditions of physiological stress, such as hypoxia, the body is more susceptible to succumb to pro-thrombotic state like those at high altitudes. Hypoxia acts as a trigger for activating the genes of coagulation cascade, regardless of the physical activity (19). Various studies have shown that hypoxia predisposes the homeostasis shift towards a pro-coagulative milieu.…”
Section: Discussionmentioning
confidence: 99%
“…However, exposure to hypoxic stress can increase the risk of developing thrombosis by hypoxia-induced platelet aggregation and activation of blood coagulation cascade (5). Hypoxia has been demonstrated to create a pro-thrombotic milieu by an increase in thrombin generation in whole blood even in absence of physical exercise (6). As platelet activation is the primary cause of hemostatsis during vascular injury, substantial evidences demonstrate platelet activation and an increase in platelet adhesiveness in healthy volunteers on exposure to hypoxia (7).…”
Section: Introductionmentioning
confidence: 99%
“…To characterize changes in their hemostatic profile, we measured VWF (total antigen, 126 VWF propeptide, 62 and active VWF) levels, FVIII, 126,127 thrombin generation, 128 fibrinogen levels, 127 platelet activation, 129 and clot lysis time 127 (methods according to references). Peripheral blood cell counts in citrated whole blood were determined using a COULTER counter analyzer (Beckman Coulter, Woerden, the Netherlands).…”
Section: Appendix: Methodology For the Pilot Studymentioning
confidence: 99%
“…(D) FVIII activity was measured as described previously. 126,127 All measurements were performed in triplicate, and data represent the mean AE standard deviation (SD) (n ¼ 5).…”
Section: Von Willebrand Factormentioning
confidence: 99%